Genetic Testing for Thrombophilia-Related Genes: Observations of Testing Patterns for Factor V Leiden (G1691A) and Prothrombin Gene “Mutation” (G20210A) - Favaloro, Emmanuel J. (Seminars in Thrombosis and Hemostasis, 2019)
Thrombophilia is a generic term that defines an increased propensity toward thrombosis and associated morbidity. Factor V Leiden (FVL; G1691A) and the prothrombin gene mutation (PGM; G20210A) comprise the most common genetic associations with thrombosis, and thus comprise the most commonly requested genetic thrombophilia investigations. This report describes an audit of local test findings that suggests growing futility in testing for FVL and PGM. Test requests for FVL and PGM were assessed for a recent period of 2.5 years (starting from 2016 to end of June 2018) from a large tertiary-level pathology provider. From a total of more than 10,000 thrombophilia-related test requests over the analysis period, 2,700 and 2,135 were, respectively, for FVL and PGM. The age ranges of patients varied across the full life span spectrum, but the peak investigation age range for the entire cohort was 30 to 39 years. Investigations were more often requested for females (> 70% of requests) than males, and the peak investigation age range for females (30–39 years) was earlier than males (50–59 years). However, proportionally more males than females were identified with FVL (15.4 vs. 6.6%) or PGM (10.4 vs. 4.3%), respectively. The age-related patterns of test ordering were also identified as closely aligned to birth patterns in females and thrombosis patterns in males. There has been a trend to annual reduction in detection of FVL mutation from a peak of more than 25% in 1996 to ∼10% in each year of the past decade, suggesting poorer patient selection. Of test-requesting indications, pregnancy/fetal morbidity was identified in 16.4% of all requests for females, and thromboembolism was identified in 21.4 and 18.0% of all requests for females and males, respectively. In terms of FVL identification, a heterozygous pattern was identified in 4.2% of women tested for pregnancy/fetal morbidity, but 11.7 and 15.1% of females and males, respectively, for thromboembolism. In comparison, the background rate of FVL detection in the general population in our geographical region is approximately 3 to 7%. Overall, better targeted patient selection for testing of FVL and PGM occurred in the male cohort based on higher relative capture of thrombophilia mutations than the female cohort. However, patient selection was not optimal in either the male or female cohorts, since the captured mutation rates were only marginally higher than the expected background population detection rate. Moreover, the decline in relative identification of FVL from overall test requests over time suggests deterioration of patient selection practices by referring physicians. Notably, tests requested in the setting of thromboembolism provided a higher likelihood of FVL detection than pregnancy/fetal morbidity. These data suggest some contemporary futility of genetic testing for FVL and PGM in the real world, and in particular, in females for indications around pregnancy/fetal morbidity, proposed to be related to poor patient selection in most instances.
Keywords: thrombophilia; factor V Leiden; FVL; Arg506Gln; R506Q; G1691A; prothrombin gene mutation; PGM; G20210A; laboratory practice